Lideran??a e desempenho da equipe de desenvolvimento de software: influ??ncia do tipo de gest??o de projetos - Garcia, Fernando Andre Zemuner (2017)
The team leadership is a topic that have been studied in the last 70 years by several authors, to understand their challenges and exploit the opportunities of the same within organizations and more recently within the design environment. The team leadership has changed considerably over the years because of changes in the culture and how businesses and designs come dealing with their employees and subordinates. Because it is an important factor for the team???s performance the leaders are changing the forma of lead, so that impose the wills and simply ordering already no longer part of the current management methods, having to be a shared leadership or based on exchanges so that the led can follow their leader. With the transformation of companies, many have adopted the Project management to develop their products or internal systems, making the leader Always seek greater adaptability to lead and generate the success or profit expected for companies. This dissertation seeks to identify the influence of the type of leadership in performance of the project team as the methods applied in the management of software development projects. The study was conducted via an online electronic questionnaire distributed to team leaders or projects members who have participated in software developments projects. After analyzing the data collected, it was identified that the project management method does not affect the existing relationship between the types of leadership studied and the performance of the team. Another important factor derived from the analysis is that transactional and transformational leadership are positively related to team performance, despite the weak relationship existing for transactional leadership, while empowerment leadership is strongly related to team performance, but in a negative way. The derivation of the analyzes is that companies working with software development projects must invest in leadership development as a measure to increase team performance, especially the transformational leaders, a style that presented the highest positive relation to team performance Among the three leaderships studied, regardless of the method of project management used.